IMPROVING THE METHODOLOGICAL SYSTEM FOR DEVELOPING INTERCULTURAL COMMUNICATIVE COMPETENCE IN SENIOR SCHOOL STUDENTS - Turdiyeva Sevara Tulkinovna (Ethiopian International Journal of Multidisciplinary Research, 2026)
This article examines the methodological foundations for developing intercultural communicative competence in senior school students. In the context of globalization, rapid digital communication, and increasing interaction among representatives of different cultures, the formation of intercultural competence has become one of the essential objectives of modern education. The study highlights the pedagogical significance of integrating language learning with cultural awareness, tolerance, empathy, and communicative flexibility. Special attention is given to the improvement of the methodological system through interactive strategies, dialogic learning, role-based communication, authentic materials, and problem-based tasks. The article substantiates that the effective formation of intercultural communicative competence in senior school students requires a systematic, student-centered, and practice-oriented approach. The proposed methodological framework contributes to the development of learners’ communicative abilities, critical thinking, and readiness for constructive intercultural dialogue.